2013
DOI: 10.1007/s13538-013-0132-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Raman Spectra of l-Histidine Crystals

Abstract: We present a Raman spectroscopy investigation of the vibrational properties of L-histidine crystals at low temperatures. The temperature dependence of the spectra show discontinuities at 165 K, which we identify with modifications in the bonds associated to both the NH 3 + and CO 2 -motifs indicative of a conformational phase transition that changes the intermolecular bonds. Additional evidence of such a phase transition was provided by differential scanning calorimetry measurements, which identified an enthal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…An additional peak at 1612 cm –1 can also be assigned to the contribution of these three amino acid residues . Other vibration modes were observed at 1091 cm –1 (CN symmetric stretching), 1175 cm –1 (CH bending in-plane), 1275 cm –1 (amide III), 1449 cm –1 (CH bending), 1714 cm –1 (CO stretching), 2930 cm –1 (aliphatic CH stretching), and 3070 cm –1 (aromatic CH stretching). ,,, High intense peaks at 440 and 611 cm –1 for ADAM17cyto indicate the presence of SS and CS stretching, respectively. , The SS stretching mode might have two contributions, the first from the disulfide bond formed in the heterodimer between Trx-1 and ADAM17cyto and another related to the disulfide bond present in the ADAM17cyto structure. Although disulfide bond formation is a slow process at physiological pH (7.4), many proteins like ADAM17cyto and Trx-1 can interact through cysteine dimerization.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…An additional peak at 1612 cm –1 can also be assigned to the contribution of these three amino acid residues . Other vibration modes were observed at 1091 cm –1 (CN symmetric stretching), 1175 cm –1 (CH bending in-plane), 1275 cm –1 (amide III), 1449 cm –1 (CH bending), 1714 cm –1 (CO stretching), 2930 cm –1 (aliphatic CH stretching), and 3070 cm –1 (aromatic CH stretching). ,,, High intense peaks at 440 and 611 cm –1 for ADAM17cyto indicate the presence of SS and CS stretching, respectively. , The SS stretching mode might have two contributions, the first from the disulfide bond formed in the heterodimer between Trx-1 and ADAM17cyto and another related to the disulfide bond present in the ADAM17cyto structure. Although disulfide bond formation is a slow process at physiological pH (7.4), many proteins like ADAM17cyto and Trx-1 can interact through cysteine dimerization.…”
Section: Resultsmentioning
confidence: 96%
“…87,88,90,91 High intense peaks at 440 and 611 cm −1 for ADAM17cyto indicate the presence of SS and CS stretching, respectively. 87,92 The SS stretching mode might have two contributions, the first from the disulfide bond formed in the heterodimer between Trx-1 and ADAM17cyto and another related to the disulfide bond present in the ADAM17cyto structure. Although disulfide bond formation is a slow process at physiological pH (7.4), many proteins like ADAM17cyto and Trx-1 can interact through cysteine dimerization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4c). The vibrational bands of the INS data of MOF-808 and MOF-808@His samples were identified on the basis of the bibliographic data based on the combination of experimental and computational studies (de Sousa et al 74 and Freire et al 75 ), as well as taking into account our preliminary studies in the MOF-808@Cys system. For instance, the assignation of the Raman and IR bands found in literature have been summarized in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prior differential scanning calorimetry (DSC) analysis of powder samples performed by Supriya et al (2018) show the absence of a phase transition in the two polymorphs between $313 and 573 K. Other studies have revealed discontinuities in the Raman spectra of the orthorhombic form at 165 K and an enthalpic anomaly at around 160 K, also by DSC (De Sousa et al, 2013), suggesting a conformational phase transition. Further and more detailed temperature-dependent diffraction work around 165 K is needed to understand fully the phase behaviour of the orthorhombic form of l-histidine.…”
Section: Neutron Structures Of the Polymorphs At 295 K And The Effect Of Temperaturementioning
confidence: 99%